The Relationship between Self-Acceptance and Flourishing among Working Students in Yogyakarta - Julistia, Lola; Agus Salim (INDONESIAN COUNSELING AND PSYCHOLOGY, 2025)
This study aims to determine the relationship between self-acceptance and flourishing among students working in Yogyakarta. Flourishing is the focus because it reflects optimal psychological well-being, which includes positive emotions, engagement, healthy social relationships, meaning in life, and achievement, all of which are important aspects for students facing the dual burden of academics and work. Self-acceptance is a primary concern because it serves as the foundation for psychological well-being, helping individuals accept their strengths and weaknesses fully, thereby increasing their resilience to pressure and stress. The study used a correlational quantitative approach with 244 student respondents aged 18-27 years. Data were collected using the Flourishing scale based on the PERMA model (Cronbach's Alpha = 0.886; 17 items) and the Self-Acceptance scale (Cronbach's Alpha = 0.793; 19 items). Analysis used normality tests, linearity tests, and Spearman's correlation. The results showed that the majority of respondents were in the moderate category for both variables, namely 89.34% for flourishing and 61.89% for self-acceptance. Spearman's correlation showed a significant positive relationship between self-acceptance and flourishing (r = 0.558; p = 0.000), with self-acceptance explaining approximately 27.7% of the variation in flourishing. These findings confirm the important role of self-acceptance in supporting the psychological well-being of working students. This study is expected to serve as the basis for developing interventions that target increasing self-acceptance to improve student flourishing.